Penyediaan kaca aerosilika daripada sekam padi - Abdullah, Rozieyati (2004)
The aim of this study is to prepare aerosilica glass from silica aerogel synthesized from rice husk. The study was carried out in order to produce a low thermal conductivity aerosilica glass that can be used as thermal insulator. Aerosilica glasses of nominal composition 5 %-55 % mol of aerogel were prepared using a mixture of aerogel, SiOz with sodium carbonate, Na2C03. The glass samples of (Si02)@a20)1, were produced using liquid melt quenchng method at the melting temperature about 1 100 "C for aerosilica glass and 1400 "C for conventional sodium silicate glass. The study shows aerosilica glass is amorphous and exhibits better properties compared to conventional sodmn silicate glass with an optimum composition.of 20 % mol aerogel with density 2.39 g cm", thermal conductivity value of 1.35 ~ m k ' and Vickers micro hardness value of 412 Hv. According to the infrared spectrum, ths phenomena can be related to the structure of Si-0-Si bonds. The presence of foams by SEM micrograph contributes to the low thermal conductivity of aerosilica glass due to the formation of a new closed pores of 8 pm to 89 pm insize. The MAS-NMR spectra indicate a larger number of bridging 2 3 oxygen with Si atom in aerosilica glass as present Q ,Q and ~"pesies. The differential thermal analyzer shows aerosilica glass can be obtained at a lower temperature range of 8 18-828 "C which is stable against corrosive agents. W-VISNIR analysis shows the samples absorbance in UV light range is related to thermal conductivity.